Concern and death anxiety during an ongoing terror wave: The moderating role of direct vs. indirect exposure. Issue 3 (16th March 2018) - Mahat-Shamir, Michal; Hamama-Raz, Yaira; Ben-Ezra, Menachem; Pitcho-Prelorentzos, Shani; Zaken, Adi; David, Udi Y.; Bergman, Yoav S.
ABSTRACT: The current study examined whether emotional concern over one's security situation is connected with death anxiety during an ongoing terror wave, and whether type of exposure (media exposure vs. contact with witnesses) moderates this connection. A total of 345 individuals, aged 18–70, were sampled during an ongoing wave of terror in Israel and filled out scales measuring death anxiety, concern over security situation, and type of exposure. Results indicated that increased concern was connected with enhanced death anxiety. Moreover, this connection was more pronounced among individuals exposed to the events through the media, in comparison with individuals who had first-hand contact with witnesses.